(3GdJWhjQ GdJfXjej (B:s (3CSGSjGJ heaGgje MOjKI (B/s - (3GddhRj, ehSis ((3YeGf(B: s (3TGQY GdLeYjI GdYdejI(B, s, 1999)
(3GdJWhjQ GdJfXjej, GdbhI hGdUQGY aj GdJfXjeGJ GdEOGQjI, GdJhJQ GdJfXjej hGdJWhjQ, GdhdGA GdJfXjej hGdJWhjQ GdJfXjej, GdESJKeGQGJ GdEOGQjI hGdJWhjQ GdJfXjej, EOGQI GdLhOI GdTGedI hGdJWhjQ GdJfXjej, GdJNGUjI hGdJWhjQ GdJfXjej, GdJWhjQ GdJfXjej aj GdCQOfs
Keywords: (3GdJWhQ GdJfXjejs; (3GdJfXjes